2005
DOI: 10.2214/ajr.04.1344
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Multisampling Core Needle Biopsy of Thoracic Lesions

Abstract: Percutaneous CT-guided coaxial multisampling large CNB of suspected thoracic lesions, in a mainly cancer-based population, is an accurate procedure for a specific histologic diagnosis and has a low rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 18 publications
3
23
0
2
Order By: Relevance
“…4,48 TTNA does have a 90% chance of confi rming a diagnosis (range, 76% to 90%), but some report a pneumothorax rate as high as 40%. 4,5,[49][50][51][52][53][54][55][56][57] Additionally, the diagnostic yield is infl uenced by the size of the lesion, the size of the needle, the number of passes, and the presence of rapid on-site evaluation. 4,5,[53][54][55][56] The location of the lesion in the lungs, peripheral vs central, may also infl uence the diagnostic yield of TTNA.…”
Section: Discussionmentioning
confidence: 99%
“…4,48 TTNA does have a 90% chance of confi rming a diagnosis (range, 76% to 90%), but some report a pneumothorax rate as high as 40%. 4,5,[49][50][51][52][53][54][55][56][57] Additionally, the diagnostic yield is infl uenced by the size of the lesion, the size of the needle, the number of passes, and the presence of rapid on-site evaluation. 4,5,[53][54][55][56] The location of the lesion in the lungs, peripheral vs central, may also infl uence the diagnostic yield of TTNA.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a tumor was located in the right side in six of seven patients with thoracic Castleman's disease. 8 Although Loubeyre et al 23 reported that they diagnosed pulmonary Castleman's disease using core needle biopsy, preoperative needle biopsy was carried out in six cases of chest wall mass; the results were nondiagnostic in all cases. All patients except ours underwent surgical exploration and subsequent removal of the mass by thoracotomy or median sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In high-volume experienced centers, typical yield can exceed 90% for both malignant and benign lesions (24,25). Core biopsies are preferred to FNA because of their higher yield, but more importantly biopsies allow evaluation of tissue architecture, and provide sufficient material for immunohistochemistry and genetic analyses.…”
Section: Ct-guided Fine-needle Aspiration and Biopsymentioning
confidence: 99%